Asymmetric Synthesis of α‐Amino Acids Bearing a 3‐Alkyloxindole Structural Motif. Issue 47 (14th December 2021) - Wang, Xiao‐Ping; Liu, Yong‐Liang; Wei, Jie; Chen, Ling‐Yan; Li, Ya
Abstract: We report a diastereoselective Mannich‐type reaction of 3‐alkyloxindole with N‐ tert ‐butanesulfinyl imino ester. This method provides a concise route to α‐amino acid derivatives bearing a 3‐alkyloxindole structural motif. This protocol has the advantage of using readily accessible starting materials and is operationally simple. A plausible transition‐state mode for the observed stereoselectivity is presented. Abstract : A diastereoselective Mannich‐type reaction of 3‐alkyloxindole with N‐ tert ‐butanesulfinyl imino ester is developed, which provides a concise route to α‐amino acid derivatives bearing a 3‐alkyloxindole structural motif. This protocol has the advantage of using readily accessible starting materials and is operationally simple. A chair‐like transition‐state mode for the observed stereoselectivity is proposed.